Role of platelet-rich plasma in maxillofacial surgery - Hifny, Sara Ahmed; Alalharith, Abdullrahman Saeed; Idrees, Mutasim Ahmad; Befle, Mohammed Ahmed; AlGarni, Shihnaz Mohammed; Alsharif, Abdullah Hassan; Alfaifi, Wafa Hadi; Dahman, Najd Musa; Alanazi, Ahmed Hassan; Allam, Mohammed Faisal; Alodiani, Mohammed Bandar (International Journal Of Community Medicine And Public Health, 2021)
Platelet-rich plasma (PRP) has been reported as an efficacious modality that can enhance the process of wound healing and tissue regeneration and has been validated in different medical settings, including cardiovascular surgery, otolaryngology, head and neck surgery, and maxillofacial surgery. In dental and oral surgery settings, PRP has been reported as an efficacious approach with favorable outcomes in different settings. Some of these procedures include surgical repair of the alveolar cleft, mandibular reconstruction, ablative surgical procedures, placement of osseointegrated implants, periodontal plastic surgery, and management of infrabony periodontal defects. In the present study, we aim to discuss the role and mechanisms that PRP plays in the settings of maxillofacial surgery based on evidence from the relevant studies in the literature. Evidence indicates the wide acceptance of the modality, which has been proven to increase the rate of wound healing and reduce the frequency of pain and swelling. The administration of PRP has been reported to dispense with the need for invasive approaches that might be furtherly associated with complications and different morbidities. However, in most of the favorable events where the PRP administration of was associated with enhanced outcomes, the modality was used in combination with another therapeutic approach. Therefore, further research is needed to validate the efficacy of the modality in the different settings.